Identifikasi Keputusan Pemberlakukan Pembatasan Sosial Berskala Besar (Psbb) Di Provinsi Dki Jakarta Tahun 2020 - Dian Sari (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2021)
The Covid-19 pandemic that is currently occurring in Indonesia, especially in the DKI Jakarta Province, began to occur at the end of February 2020. This pandemic has made changes in various sectors, this indicates that the conditions that occur during a pandemic are conditions that cannot be predicted. Mr. Anies Baswedan as the Governor of Indonesia's capital city has a very big role in making effective decisions during this pandemic. One of the keys to the success of a leader is making an effective decision. In this research, it tries to describe the style of decision making by the Governor of DKI Jakarta during the Covid-19 Pandemic conditions. The research method used is qualitative research techniques with descriptive analysis methods, data collection using literature study. Based on data analysis, the decision to enforce the PSBB (Large-Scale Social Restrictions) is essentially very important and constitutes an informative, unprogrammed decision on decentralization based on facts and intuition.